2023
DOI: 10.1021/acsami.2c20776
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Polyphenol and LL-37 Peptide-Modified Nanofibrous Scaffolds for Promotion of Antibacterial Activity, Anti-Inflammation, and Type-H Vascularized Bone Regeneration

Abstract: The regeneration of oral tissues is a challenging clinical problem because of the complex microbial and biological stress environments. Electrospun fibrous scaffolds have attracted significant interest as effective barrier membranes for guided bone regeneration (GBR); however, no mature strategy yet exists for the surface modification of fibers to provide versatility to satisfy clinical requirements. This study demonstrated a practical biosafety strategy: the combined use of plant polyphenols and LL-37 peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 67 publications
3
14
0
Order By: Relevance
“…These results further confirmed that DTS modified with TA exhibited anti-inflammatory effects by modulating macrophage polarization. 36,62 Overall, the results of the in vivo and in vitro experiments were consistent and confirmed the tendency of TAmodified DTS to modulate macrophage polarization toward the M2-type.…”
Section: Antioxidant Activity Evaluation Of the Scaffold As Shown In ...supporting
confidence: 70%
See 2 more Smart Citations
“…These results further confirmed that DTS modified with TA exhibited anti-inflammatory effects by modulating macrophage polarization. 36,62 Overall, the results of the in vivo and in vitro experiments were consistent and confirmed the tendency of TAmodified DTS to modulate macrophage polarization toward the M2-type.…”
Section: Antioxidant Activity Evaluation Of the Scaffold As Shown In ...supporting
confidence: 70%
“…The results of macrophages' cytoskeleton were consistent with those obtained from brightfield microscopy (Figure 5B), demonstrating that DTS and DTS-TA 0.1 enhanced the phenotype of M2 macrophages and that DTS-TA 0.1 had a more pronounced effect. 36 As depicted in Figure 5C, macrophages exhibited an upregulation of CD86 expression in the presence of LPS and an induction of Arginase-1 (Arg-1) expression when exposed to IL-4. The DTS-TA 0.1 group showed a higher level of Arg-1 expression than that of the DTS group, while the trend of CD86 expression was the opposite.…”
Section: Antioxidant Activity Evaluation Of the Scaffold As Shown In ...mentioning
confidence: 88%
See 1 more Smart Citation
“…Compared with LbL multilayer films obtained by dipping, brushed films showed oriented collagen fibers along the brushing direction, which was favorable for the alignment and differentiation of human myoblasts. Jin et al 58 modified the electrospun fibrous scaffold with TA first and then with LL-37 peptides, and in vitro experiments showed that the modified fibrous scaffold had strong antibacterial, enhanced angiogenesis, anti-inflammatory, and type-H vascularized bone regeneration, indicating that the modified fibrous scaffold had great potential application in guiding bone regeneration.…”
Section: Protein-polyphenol Coatingsmentioning
confidence: 99%
“…Natural AMPs, however, possess various drawbacks, such as toxicity to the host, and loss of effectiveness in physical concentrations of salt and serums . Peptides that are rationally designed may be able to diminish these drawbacks in natural peptides to some extent. …”
Section: Introductionmentioning
confidence: 99%